2007
DOI: 10.2151/jmsj.85a.73
|View full text |Cite
|
Sign up to set email alerts
|

Validating Basic Surface Variables in the Australian Bureau of Meteorology Model with CEOP EOP3 In-situ Data

Abstract: The Coordinated Enhanced Observing Period (CEOP) Project has initiated the collection of model output location time series (MOLTS) data from numerical weather prediction and assimilation centers, including the Australian Bureau of Meteorology. These were designed to complement the collection of insitu observational data sets at the same 41 locations. This study is a preliminary attempt to assess the differences and similarities between the MOLTS and time series of the in-situ data. The MOLTS from the Bureau's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In general, comparisons of the analyses from the NWPCs have primarily been through the single-point Model Output Location Time Series (MOLTS) collocated with CEOP reference sites or through considering only one model system (Yang et al 2007;Chou et al 2007;Rikus 2007;Milton and Earnshaw 2007;Hirai et al 2007;Meinke et al 2007;Kato et al 2007;Bosilovich et al 2007). To get at the comparison of global grids, an ensemble of the analyses was developed for several purposes.…”
Section: Methodsmentioning
confidence: 99%
“…In general, comparisons of the analyses from the NWPCs have primarily been through the single-point Model Output Location Time Series (MOLTS) collocated with CEOP reference sites or through considering only one model system (Yang et al 2007;Chou et al 2007;Rikus 2007;Milton and Earnshaw 2007;Hirai et al 2007;Meinke et al 2007;Kato et al 2007;Bosilovich et al 2007). To get at the comparison of global grids, an ensemble of the analyses was developed for several purposes.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison between CEOP MOLTS (Model Output Location Time Series) and the in situ observations has been conducted with the goal of improving representations of the key physical processes in the model [4][5][6][7]. Studies have shown that most climate models underestimate the variation of daily temperature and have poor ability in simulating precipitation (namely, with high systematic biases), and that model simulation biases change with the underlying surface, with the largest bias in the tropical oceans [8][9][10][11]. As for the dry period at the Rondonia CEOP reference site in Brazil, the CPTEC (Centro de Previsão de Tempo e Estudos Climáticos) model always overestimates precipitation, while the meso-scale Eta Model always overestimates near-surface temperature [12].…”
Section: Introductionmentioning
confidence: 99%